(untitled) (AYUSHDHARA, 2025)
Dincharya, an ancient Ayurvedic daily regimen, is essential for holistic well-being and encourages physical and mental harmony by addressing the mind, soul, sensory organs, digestion, bodily humours (Dosha), tissue (Dhatu), and waste (Mala). Neglecting it has led to a surge in ailments like hypertension and diabetes. Dincharya include waking in Bhrama-muhutra, Dantadhawana, Jihva nirlekhan, Nasya, Kavala, Abhyanga, Sadvritta and Bhojana. Its core objective is to proactively maintain health and ward off illnesses through a structured routine. Each practice within Dincharya holds significance in nurturing different aspects of health. Rising during Brahma-muhurta leverages cortisol hormone peak for anti-stress, immunity, and metabolism. Kavala reduces plaque and enhances oral health. Abhyanga regulates circadian rhythm, promoting better sleep. Vyayama improves physical fitness, cognition, and cardiovascular health. Nasya boosts immunity and fights respiratory infections. Neglecting Dincharya compromises immunity and metabolic function, paving the way for health concerns. In conclusion, Dincharya’s timeless wisdom offers a blueprint for optimal health and disease prevention. Embracing this holistic approach fosters resilience against modern ailments. It serves as a beacon, guiding individuals back to holistic health and vitality in a world often swayed by quick-fix solutions.